Identification of dysregulated pathways through SLC30A8 protein interaction in type 1 diabetes mellitus - Afreen Bhatty; Zile Rubab; Hafiz Syed Mohammad Osama Jafri; Sheh Zano (AIMS Molecular Science, 2021)
Objective: The aim of the current study was to explore the gene enrichment and dysregulated pathways on the basis of interaction network analysis of SLC30A8 in type 1 diabetes mellitus (T1DM). SLC30A8 polymorphism could be characterized as a beneficial tool to identify the interacting gene in developing T1DM.